Qualifications of information specialists: case of library and information students at the Department of Information Science, Faculty of Philosophy, Universty of Zagreb, Croatia - Afrić, Vjekoslav; Lasić-Lazić, Jadranka; Badurina, Boris Dragija Ivanović, Martina; Golub, Koraljka (2002)
The results of this short research are a confirmation to the hypothesis that stretches throughout the area of information science and refers to the fact that knowledge of an information expert is one of the most volatile ones. Based on the analysis of four-year students' answers several areas not sufficiently present in the Department's educational programme were sorted out. Students primarily pointed to the problem of quality practicums that are, in their opinion, insufficiently covered by the programme. The same is true for courses dealing with computers in general. This primarily refers to the need to get acquainted with the area of programming and applications that are basic for the profession, as well as to introducing the courses on marketing and communicology. What students can expect is knowledge and skills that would prepare them and direct them for acquiring knowledge specific for a variety of working environments, knowledge for adaptation and development, which calls for constant development and growth.
Projekt MZOS
ENG